UPAYA MENINGKATKAN KUALITAS KEHIDUPAN KERJA GURU SEKOLAH DASAR - Laura F.N. Sudarnoto (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2010)
Abstract: Efforts of improving quality of work life of elementary schools' teachers. A quality of education can be more determined by a quality of educator than amount of educational fund and completeness of facilities. Results of the research on 363 sample of state elementary teachers  and private elementary teachers in Jakarta showed that self confidency, commitment towards career as teachers, and competencies of class management given direct effect on quality of work life of  elementary schools'teachers. The efforts of improving quality of work life, specifically of  elementary schools' teachers can be conducted through a variety of activities, such as conducting an activity quality task force (eg. KKG, MGMP) continually so they can improve their  that self confidency, conducting enrichment of competencies through action research so they can improve their class management competencies, and improving their profesional competencies by following teachers profession education program. Efforts that is needed conducting by government is activating Institution of Educational Quality Assurance so teachers can be monitored dan evaluated programed dan responsible.   Abstrak: Kualitas pendidikan lebih ditentukan oleh kualitas pendidiknya dan bukan oleh besarnya dana pendidikan dan juga bukan oleh kelengkapan sarana. Hasil penelitian pada 363 sampel guru SD negeri dan swasta di Jakarta menunjukkan bahwa kepercayaan diri, komitmen terhadap karir sebagai guru, dan kemampuan mengelola kelas memberikan efek langsung terhadap kualitas kehidupan kerja guru SD. Usaha meningkatkan kualitas kehidupan kerja, khususnya guru SD, dapat dilakukan dengan berbagai kegiatan, antara lain melakukan aktivitas gugus kualitas (misalnya: KKG, MGMP) secara kontinu agar dapat meningkatkan kemampuan dan kepercayaan dirinya, melaksanakan pemerkayaan kompetensi melalui penelitian tindakan kelas sehingga kemampuan mengelola kelasnya dapat lebih baik, dan menambah kompetensi profesional dengan mengikuti program Pendidikan Profesi Guru. Usaha yang perlu dilakukan dari pihak pemerintah adalah mengaktifkan Lembaga Penjaminan Mutu Pendidikan (LPMP) agar melakukan monitoring dan evaluasi secara terprogram dan bertanggungjawab.